Solar Vapor Generation: Low‐Cost and High‐Efficiency Solar‐Driven Vapor Generation Using a 3D Dyed Cotton Towel (Global Challenges 9/2019). Issue 9 (9th September 2019) - Yang, Yudi; Sui, Yujin; Cai, Zaisheng; Xu, Bi
Abstract : In article number1900004, Bi Xu and co‐workers design an easy‐to‐manufacture, low‐cost, and highly reliable solar‐driven evaporator for water purification using a black cotton towel with a hollow conical shape. The reactive dye molecules diffuse into the cotton and form strong covalent bonds with the fiber after dyeing, which firmly fixes light‐absorbing materials on the substrate.